Efficient Shape Formation by 3D Hybrid Programmable Matter: An Algorithm for Low Diameter Intermediate Structures - Hinnenthal, Kristian; Liedtke, David Jan; Scheideler, Christian (3rd Symposium on Algorithmic Foundations of Dynamic Networks (SAND 2024))
This paper considers the shape formation problem within the 3D hybrid model, where a single agent with a strictly limited viewing range and the computational capacity of a deterministic finite automaton manipulates passive tiles through pick-up, movement, and placement actions. The goal is to reconfigure a set of tiles into a specific shape termed an icicle. The icicle, identified as a dense, hole-free structure, is strategically chosen to function as an intermediate shape for more intricate shape formation tasks. It is designed for easy exploration by a finite state agent, enabling the identification of tiles that can be lifted without breaking connectivity. Compared to the line shape, the icicle presents distinct advantages, including a reduced diameter and the presence of multiple removable tiles. We propose an algorithm that transforms an arbitrary initially connected tile structure into an icicle in 𝒪(n³) steps, matching the runtime of the line formation algorithm from prior work. Our theoretical contribution is accompanied by an extensive experimental analysis, indicating that our algorithm decreases the diameter of tile structures on average.
Keywords: Programmable Matter; Shape Formation; 3D Model; Finite Automaton

Interdisziplinäre Verständigung als Baustein wissenschaftsdidaktischer Kompetenz - Jenert, Tobias; Scharlau, Ingrid (Wissenschaftsdidaktik IV: Wissenschaftskommunikation)
Wir beschreiben den Versuch, »Verständigungskompetenzen« im Sinne von Ludwig Huber in der Graduiertenförderung zu entwickeln. Verständigung ist für Huber integraler Bestandteil wissenschaftlicher Erkenntnis. Wissenschaftler:in- nen werden aber in die Praktiken ihrer Disziplin hineinsozialisiert; die dabei entstehen- de disziplinäre Identität und ihre Selbstverständlichkeiten sind zentral für Teilhabe am Wissenschaftssystem. Das erschwert Verständigung prinzipiell, insbesondere das Nach- vollziehen der Wahrnehmungen und Sinnkonstruktionen der Adressat:innen des eige- nen Wissenschaftshandelns. Ausgehend von der Beobachtung, dass Doktorand:innen ihre Disziplin als selbstverständlichen Zugang zum Gegenstand betrachten, stellen wir das Konzept einer Sommerschule vor, das darauf zielt, die Abstraktion von der eigenen disziplinären Perspektive zu ermöglichen, Systemwissen fördert und Verständigungs- prozesse anstößt.
Keywords: science communication; Wissenschaftskommunikation; Wissenschaftsdidaktik; young researchers; Nachwuchsförderung

Universal Coating by 3D Hybrid Programmable Matter - Kostitsyna, Irina; Liedtke, David Jan; Scheideler, Christian (Structural Information and Communication Complexity)
Motivated by the prospect of nano-robots that assist human physiological functions at the nanoscale, we investigate the coating problem in the three-dimensional model for hybrid programmable matter. In this model, a single agent with strictly limited viewing range and the computational capability of a deterministic finite automaton can act on passive tiles by picking up a tile, moving, and placing it at some spot. The goal of the coating problem is to fill each node of some surface graph of size n with a tile. We first solve the problem on a restricted class of graphs with a single tile type, and then use constantly many tile types to encode this graph in certain surface graphs capturing the surface of 3D objects. Our algorithm requires O(n^2) steps, which is worst-case optimal compared to an agent with global knowledge and no memory restrictions.
Keywords: Programmable Matter; Coating; Finite Automaton; 3D

Ion‐Dependent Stability of DNA Origami Nanostructures in the Presence of Photo‐Generated Reactive Oxygen Species - Rabbe, Lukas; Garcia‐Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (Small Structures)
DNA origami nanostructures are promising carries for drug delivery applications. However, their limited stability under relevant conditions often presents a challenge. Herein, the structural stability of DNA origami nanostructures is investigated in a setting compatible with their application in photodynamic therapy (PDT). To this end, DNA origami triangles and six‐helix bundles (6HBs) are loaded with the clinically tested photosensitizer methylene blue, which upon irradiation with red light generates reactive oxygen species (ROS) that attack the DNA origami nanostructures. ROS‐induced structural damage is observed to depend on the ionic composition of the surrounding medium and becomes more severe at low ionic strength. Mg 2+ ions can efficiently protect the DNA origami nanostructures from ROS‐induced damage and may even heal some of the damage obtained under Mg 2+ ‐free conditions when added after irradiation. Finally, the employed DNA origami 6HBs are more resistant toward ROS‐induced structural damage than the triangles, which is attributed to their markedly different mechanical properties. These results thus provide some fundamental insights into the stabilizing role of DNA origami superstructure that may guide the selection or design of DNA origami nanocarriers with optimized stability for their application in PDT.

Theorien des digitalen Kapitalismus. Arbeit, Ökonomie, Politik und Subjekt - Quast, Julia (Zeitschrift für Genozidforschung)

Tagungsbericht: "Und was hat das mit mir zu tun?“ – Zugänge zur Tradition in der islamischen Religionspädagogik. 01.12. - 02.12.2023, Paderborn. - Candan, Ayse Beyza

Schul(innen)räume und Verhaltensnormierung in Franckes Schulstadt - Süßmann, Johannes (Frühneuzeitliche Schularchitekturen. Internationale und interdisziplinäre Perspektiven)

Kinderperspektiven auf Raum in der inklusiven Grundschule - Bunte, Charline (Zeitschrift für Inklusion)

Estimation of losses caused by sidewall roughness in thin-film lithium niobate rib and strip waveguides - Hammer, Manfred; Babel, Silia; Farheen, Henna; Padberg, Laura; Scheytt, J. Christoph; Silberhorn, Christine; Förstner, Jens (Optics Express)
Samples of dielectric optical waveguides of rib or strip type in thin-film lithium niobate (TFLN) technology are characterized with respect to their optical loss using the Fabry-Pérot method. Attributing the losses mainly to sidewall roughness, we employ a simple perturbational procedure, based on rigorously computed mode profiles of idealized channels, to estimate the attenuation for waveguides with different cross sections. A single fit parameter suffices for an adequate modelling of the effect of the waveguide geometry on the loss levels.
Keywords: tet_topic_waveguide

From Swiss-cheese to discrete ferroelectric composites: assessing the ferroelectric butterfly shape in polarization loops - Myroshnychenko, Viktor; Mulavarickal Jose, Pious Mathews; Farheen, Henna; Ejaz, Shafaq; Brosseau, Christian; Förstner, Jens (Physica Scripta)
We explore the polarization hysteretic behaviour and field-dependent permittivity of ferroelectric-dielectric 2D materials formed by random dispersions of low permittivity inclusions in a ferroelectric matrix, using finite element simulations. We show how the degree of impenetrability of dielectric inclusions plays a substantial role in controlling the coercive field, remnant and saturation polarizations of the homogenized materials. The results highlight the significance of the degree of impenetrability of inclusion in tuning the effective polarization properties of such ferroelectric composites: coercive field drops significantly as percolation threshold is attained and remnant polarization decreases faster than a linear decay.
Keywords: tet_topic_ferro

On the repulsion effect of coupled Lamb waves modes - Nicolai, Marcel; Bulling, Jannis; Lugovtsova, Yevgeniya; Zeipert, Henning; Prager, Jens; Henning, Bernd

Diagnostics and Prognostics for Retrofitted Systems: A Comprehensive Approach for Enhanced System Health Assessment - Bender, Amelie; Aimiyekagbon, Osarenren Kennedy; Sextro, Walter (Proceedings of the 2024 Prognostics and System Health Management Conference (PHM))
Predicting the remaining useful life of technical systems has gained significant attention in recent years due to increasing demands for extending the lifespan of degrading system components. Therefore, already used systems are retrofitted by integrating sensors to monitor their performance and functionality, enabling accurate diagnosis of their condition and prediction of their remaining useful life. One of the main challenges in this field is identified in the missing data from the time where the retrofitted system has already run but without being monitored by sensors. In this paper, a novel approach for the combined diagnostics and prognostics of retrofitted systems is proposed. The methodology aims to provide an accurate diagnosis of the system’s health state and estimation of the remaining useful life by a combination of a machine learning and expert knowledge. To evaluate the effectiveness of the proposed methodology, a case study involving a retrofitted system in an industrial setting is selected and applied. It is demonstrated that the approach effectively diagnose the current system’s health state and accurately predict its remaining useful life, thereby enabling predictive maintenance and decision-making. Overall, our research contributes to advancing the field of condition monitoring for retrofitted systems by providing a comprehensive methodology that addresses the challenge of missing data.
Keywords: retrofit; diagnosis; prognostics; RUL prediction; missing data; ball bearings

Krieg aus Perspektive des Christentums. Dürfen Christ:innen Krieg rechtfertigen? - Leven, Eva-Maria; Grössl, Johannes (RELIGION 5-10)

𝜆Grapher: A Resource-Efficient Serverless System for GNN Serving through Graph Sharing - Hu, Haichuan; Liu, Fangming; Pei, Qiangyu; Yuan, Yongjie; Xu, Zichen; Wang, Lin (Proceedings of the ACM Web Conference (WWW))

Von der Entwicklung von Open Educational Resources zur Umsetzung von Open Educational Practices in der inklusiven Lehrkräftebildung: Anforderungen und Lösungswege am Beispiel der Projekte Inklud.nrw und InDigO - Büker, Petra; Kamin, Anna-Maria; Glawe, Katrin; Herding, Jana; Schaper, Franziska (MedienPädagogik)

IPA: Inference Pipeline Adaptation to Achieve High Accuracy and Cost-Efficiency - Ghafouri, Saeid; Razavi, Kamran; Salmani, Mehran; Sanaee, Alireza; Lorido Botran, Tania; Wang, Lin; Doyle, Joseph; Jamshidi, Pooyan (Journal of Systems Research (JSys))

Teaching and Learning of Microgrids for Secondary School Learners – a Renewable Energy Sustainability Strategy for East African Communities - Bogere, Paul; Belov, Alexander; Temmen, Katrin (Proceedings - First International Conference on Sustainable Energy Education (SEED 2024))

On restricted averages of Dedekind sums - Minelli, P.; Sourmelidis, A.; Technau, Marc (Int. Math. Res. Not. IMRN)

A Didactic Framework for Microgrids Knowledge Transfer – The Case of East Africa - Bogere, Paul; Temmen, Katrin (2024 IEEE Global Engineering Education Conference (EDUCON))

Brauchen wir ein ESE-Curriculum in der inklusiven Schule? – Ein Exkurs in die Konzeption eines Mehrebenenansatzes zur Prävention von Verhaltensproblemen in der Sekundarstufe I - Zdoupas, Philippos (ESE 6 (2024): In den Fokus ver-rückt – hidden topics im Förderschwerpunkt Emotionale und Soziale Entwicklung)
Die überdauernd hohen Prävalenzraten von Verhaltensstörungen und -problemen im Kindes- und Jugendalter verweisen auf einen verstärkten pädagogischen Handlungsbedarf und unterstreichen die Bedeutsamkeit präventiver Maßnahmen in der Schule. Wenngleich metaanalytische Befunde die grundsätzliche Wirksamkeit evidenzbasierter Präventionsprogramme bestätigen, so scheint der strukturelle Transfer in die pädagogische Praxis oftmals erschwert. Mit dem vorliegenden Beitrag werden die ersten konzeptionellen Ansätze eines schulweiten und curricular verankerten Präventionskonzepts zur Förderung emotionaler und sozialer Kompetenzen unter Berücksichtigung zweier methodischer Zugänge nachgezeichnet.